How Children Form and Update Beliefs from an Evidence Series - Schlottmann, Anne (Pontificia Universidad Javeriana, 2018)
Our attitudes/beliefs typically develop gradually, with information appearing over time. This study considered how 6- and 9-year-olds (N = 80) form beliefs from serial information, and how information order affects this, in parallel social and physical judgment tasks. Children updated their beliefs continuously, after each bit of information, or gave one judgment at the end of the series. Updating results showed strong, short-term recency effects; stable beliefs, reflecting all informers, developed as well. These stable beliefs were weaker for younger children; the recency was stronger. Both ages used a running average strategy when serially updating judgments, but a memory-based approach when responding only at the end. The latter produced no recency or age differences and led to stronger beliefs. It is concluded that children use the same serial judgment strategies as adults. Process parameters, e.g., recency weights, change with development/information complexity, but even young children form serial beliefs effectively.